Prevalence, Awareness, Treatment, and Control of Hypertension and Its Risk Factors in (Central) Vietnam - Ho Anh Hien; Nguyen Minh Tam; Vo Tam; Anselme Derese; Dirk Devroey (International Journal of Hypertension)
Introduction. The objective of this study is to describe the prevalence, awareness, treatment, and control of hypertension and its associated risk factors in (Central) Vietnam. Methods. In this cross-sectional study, a multistage sampling was used to select 969 participants from the general population aged from 40 to 69 years. The cardiovascular risk factors were collected throughout the interviews with a standardized questionnaire. Multivariate logistic regression analysis was conducted to test the relationship between the prevalence, awareness, treatment, and control of hypertension and the prevalence of risk factors. Results. The prevalence of hypertension was 44.8%. It was higher in men than in women (51.3% versus 39.7%, p < 0.001). In total 67.3% (74.5% in women, 60.1% in men; p = 0.001) of the participants were aware of their hypertension, 33.2% (37.5% in women, 28.9% in men; p = 0.01) of the participants were treated, and 12.2% (16.7% in women, 7.8% in men; p < 0.001) of the hypertensive participants’ hypertension was controlled. Age, gender, place of residence, body mass index, and diabetes were found to be independent risk factors for hypertension. Conclusion. The prevalence of hypertension in Vietnam is high, and the proportion of treated and controlled patients is rather low.